- Back to Home »
- c++ , decrement , difference , increment , post , pre »
- Difference between post increment, decrement and pre increment,decrement

Posted by : Waqas Javed
Sunday, 12 October 2014

Most of the new programmers are stuck between post and pre increment.

What is the difference between ++a and a++. This post will clear your confusion.

++a is a pre increment type in which first of all 1 is added in a and then its value is considered in expression. where ever in pre increment type that is a++ first of all a value is considered for expression than 1 is added to a.

Did'nt Understand?? this example will make the idea clear.

if a = 3;

b = ++a; (In this case there is pre-increment a will increase and then its value is returned to b so b will be 4 and a will also become 4)

if a = 3;

b = --a; (In this case there is pre-decrement a will first decrease and then its value is returned to b. so b will be equal to 2 and a also will be 2)

if a = 3;

b = a++ (In this case there is post-increment a value will be returned to b and then a will increase by 1 that is b will be 3 and a will become 4)

if a = 3;

b = a-- (In this case there is post-decrement a value will be returned to b and then a will decrease by 1 that is b will be 3 and a will become 2)

What is the difference between ++a and a++. This post will clear your confusion.

++a is a pre increment type in which first of all 1 is added in a and then its value is considered in expression. where ever in pre increment type that is a++ first of all a value is considered for expression than 1 is added to a.

Did'nt Understand?? this example will make the idea clear.

if a = 3;

b = ++a; (In this case there is pre-increment a will increase and then its value is returned to b so b will be 4 and a will also become 4)

if a = 3;

b = --a; (In this case there is pre-decrement a will first decrease and then its value is returned to b. so b will be equal to 2 and a also will be 2)

if a = 3;

b = a++ (In this case there is post-increment a value will be returned to b and then a will increase by 1 that is b will be 3 and a will become 4)

if a = 3;

b = a-- (In this case there is post-decrement a value will be returned to b and then a will decrease by 1 that is b will be 3 and a will become 2)